Intestinal glucose absorption capability of high, medium and non-laying birds - MAJUMDAR, S; PANDA, J N (The Indian Journal of Animal Sciences, 2013)
Intestinal glucose uptake was measured in vivo using ligated upper ileum in high, medium and nonlaying RIR birds.The biochemical changes in blood and absorbing cells of intestine of these birds were also studied. Significanlly higher glucose absorption by the intestine was observed in the birus, laying either 50%(medium) orno eggs (non-layer). Significant increase in the activity of alkaline phospbatase in the mucosalhomogenstes, prepared from the non-ligated ileum, was observed in these groups also. No significant difference in egg-yolk cholesterol was observed between medium and high laying birds although them wasa sharp increase in plasma cholesterol level in non-layers which declined in the egg-producing birds. Rateof lay did not change the plasma glucose concentration though higher plasma proLein concentrations werefound in high producing birds.